Analisis Konflik Sosial Pada Tokoh Novel Digdaya Karya Syafruddin Pernyata: Kajian Sosiologi Sastra - Anitasari, Indah; Setyawati, Meita; Agustian, Jaka Farih (Adjektiva: Educational Languages and Literature Studies, 2019)
The research on the Digdaya novel by Syafruddin Pernyata aims to describe the characters and characterizations as well as social conflicts that occur in society. Characters and characterizations, namely Mustaqim, Fajar Kelana, and Bunga Nirwana as the main characters and there are 36 additional characters, Mustaqim has a protagonist character, Fajar Kelana has a tritagonist character and Bunga Nirwana has a protagonist character. The results of the Digdaya novel research can be concluded that the form of social conflict leads to a dispute or conflict between two forces, namely an argument between Fajar Kelana and his lover Bunga Nirwana because Fajar asked to marry secretly but Bunga refused. The cause of social conflict occurs because of the difference in interests between Fajar Kelana and Mustaqim, hearing the requirements that must be met, according to him, these requirements are unreasonable, causing misunderstandings between characters. Resolution of conflict of consciousness between characters to forgive each other through WhatsApp messages sent by Fajar Kelana character. The impact of social conflict leads to the effects of disputes, namely personality changes. Fajar lived a happy life and managed to get his dream lover, Bunga Nirwana.